2019
DOI: 10.1177/0959683619887419
|View full text |Cite
|
Sign up to set email alerts
|

Steady transformation of primeval forest into subalpine pasture during the Late Neolithic to Early Bronze Age (2300−1700 BC) in the Silvretta Alps, Switzerland

Abstract: The question of the origin of Alpine farming and pastoral activities associated with seasonal vertical transhumance and dairy production in the Silvretta Alps (Eastern Switzerland) has recently benefitted from renewed interest. There, pastoral practises began during the Late Neolithic (2300 BC), but alpine dairy farming was directly evidenced so far only since the Late Bronze Age/Early Iron Age (1300–500 BC). The vegetation development, timberline shifts at 2280 m a.s.l. and environmental conditions of the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
1
14
0
1
Order By: Relevance
“…This would be in agreement with many other studies, which found evidence for first pasture use at high altitudes in the Alps, beginning in the Bronze Age (e.g. Dietre et al, 2012, 2020; Drescher-Schneider, 2009; Festi et al, 2014; Mandl, 2006; Putzer et al, 2016; Walsh and Mocci, 2011; Walsh et al, 2007; Wick et al, 2003). Archaeological and dendrochronological studies from several sites in Tyrol in Austria show, that the Bronze Age was also a period of intensive copper mining in the Northern Alps (Pichler et al, 2009, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This would be in agreement with many other studies, which found evidence for first pasture use at high altitudes in the Alps, beginning in the Bronze Age (e.g. Dietre et al, 2012, 2020; Drescher-Schneider, 2009; Festi et al, 2014; Mandl, 2006; Putzer et al, 2016; Walsh and Mocci, 2011; Walsh et al, 2007; Wick et al, 2003). Archaeological and dendrochronological studies from several sites in Tyrol in Austria show, that the Bronze Age was also a period of intensive copper mining in the Northern Alps (Pichler et al, 2009, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The strong decrease in Arboreal Pollen at the begin of LPAZ 2b at 750 BC indicates strong human impact on the vegetation around the peatland. The amount of Arboreal Pollen drops below 75%, which according to Magny et al (2006) and Dietre et al (2020) represents a threshold value for open landscapes. Since the peatland is situated well below the tree line, climatic factors cannot be made responsible for these changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pastoral fires are commonly used in mountainous areas of Europe where transhumance systems have developed. The intentional use of fire to maintain high-altitude pastures is clearly documented in the nearby region of the Alps from at least the Bronze Age (Gilck and Poschlod, 2019; Gobet et al, 2003) or even as early as the Neolithic (Dietre et al, 2020; Hafner and Schwörer, 2018; Pini et al, 2017). Unlike the Alps, the absence of a treeless zone in Šumava makes such activity less likely or at least limited to open vegetation on peat bogs.…”
Section: Discussionmentioning
confidence: 99%